The Psychological Motives of Self-Harm Behavior among Inmates at the Correctional and Rehabilitation Centers in Jordan - Alshawashreh, Omar (Jordan Journal of Educational Sciences, 2010)
The aim of this study was to investigate the psychological motives of self-harm behavior among inmates in the correctional and rehabilitation centers of Jordan. The sample consisted of (136)male and female inmates who met all criteria established for this study. For answering the research questions, the researcher developed the Motives of Self-Harm Behavior Inventory. To test the reliability of this instrument, the researcher administered this instrument to 40, male and female inmates outside the sample of the study. The internal consistency was (0.95)as measured by Cranach’s alpha, which is an indicator of reliability. The feedback of specialized professors regarding the validity of the instrument provided the face validity. The results indicated that self-harm behavior associated with stressful life events such as mental illness, dealing with prison environment, and lack of family support or bonding. No significant differences were found between inmates regarding their motives for intentional selfharm due to gender, age, and length of sentence, marital status, and convicted or waiting trials. The prevalence of selfharm behavior among male inmates was 2% and 8.5 % for females. Mental illness was the most influential and leading factor for intentional self-harm behavior especially among female inmates.